Pupils who are 'talented' in sport: narratives in and out of school - Salt, Victoria (2016)
The current White Paper Educational Excellence Everywhere (DfE, 2016) states that it is crucial for schools to build pupils’ characters and their sense of resilience to enable them to be confident in their future careers. This dissertation explores ‘talented’ pupils’ experiences and perceptions of the relationship between their school, sport and home. Whilst there is a small body of research on talented sporting pupils, very little addresses the topic from a pupil voice perspective, as this dissertation does. Narrative enquiry methodology (Connelly and Clandinin, 1990), involving timelines and semi-structured interviews (Patterson, 2012), was used with five pupils between the ages of 11 and 16 who had been identified as talented in sport. This was in order to facilitate the exploration of the project’s research questions relating to talented pupils’ perceptions and experiences of their school, home and sport and also to suggest how they might be better supported. This dissertation concludes that school is an important place for talented pupils in terms of developing friendships and that the pupils do express a positive attitude towards school. However, talented pupils receive inconsistent support from their teachers and experience a lack of communication between the school/home/pupil/coach. The pupils also indicate that the school could support them more. I propose a series of practical suggestions as to how talented pupils can be supported both in and out of school.